Cost-effectiveness of perioperative durvalumab plus neoadjuvant chemotherapy for muscle invasive bladder cancer in the United States - Caicong You; Jiahao Zhang; Jianying Lei; Wu Fu; Maobai Liu; Hongfu Cai; Bin Zheng; Na Li (Therapeutic Advances in Medical Oncology)
Background: The management of muscle-invasive bladder cancer (MIBC) remains challenging. The phase III NIAGARA trial showed that adding durvalumab to neoadjuvant chemotherapy significantly enhances event-free and overall survival for MIBC patients. However, due to the high cost of durvalumab, assessing its cost-effectiveness is crucial. Objective: To compare the cost-effectiveness of durvalumab with neoadjuvant chemotherapy versus neoadjuvant chemotherapy alone in operable MIBC, from the perspective of U.S. healthcare payers. Design: A model-based pharmacoeconomic evaluation. Method: A Markov model was constructed using data from the NIAGARA trial. Costs and utility were sourced from public databases and literature. Total costs, life-years, quality-adjusted life year (QALY), and incremental cost-effectiveness ratio (ICER) were evaluated. Sensitivity analysis assessed model robustness. Results: Compared to neoadjuvant chemotherapy alone, the combination of durvalumab with neoadjuvant chemotherapy results in an additional 0.68 QALY, with an incremental cost of $86,485.19. The ICER per QALY is $93,693.79. Sensitivity analysis demonstrated the robustness of the model. Conclusion: From the perspective of U.S. payers, durvalumab combined with neoadjuvant chemotherapy is a cost-effective strategy compared to chemotherapy alone for treating operable MIBC.